WORDWALL AS AN EDUCATIVE GAME IN ARABIC WRITING DURING COVID-19 PANDEMIC - Sa`diyah, Halimatus; Wahyudi, Asis (Proceeding of International Conference on Islamic Education (ICIED); Vol 6 No 1 (2021): Proceeding of International Conference on Islamic Education (ICEID), 2021)
This current study concerns the implementation of wordwall as an educative game in Arabic writing class during the Covid-19 pandemic. More specifically, the study aimed to describe the use of wordwall in Arabic writing and investigate students' level of Arabic writing skills by using the game during the pandemic. It employed Classroom Action Research (CAR). The participants of the study were the first-semester students in Class Ps1 taking an Arabic course organized by the Language Center of UIN Maulana Malik Ibrahim Malang (LC UIN Malang). By using CAR's model of Kemmis and Mc Taggart, the study applied two cycles. In each cycle, the researcher applied the CAR procedure sequentially; planning, acting and observing, and reflecting. Data were collected through observation, tests, and documentation. The minimal score to pass the test of Arabic writing for each student is 60, with the used range score between 0-100, and the success of the teaching is indicated by 85% of students passing the test. The average score of the initial Arabic writing test was 60, with only 60, 9% of students passed the test. In the first cycle, the average score for the Arabic writing test was 70, with the percentage of students passing the test of 73, 2%. The following cycle showed a significant increase on the average Arabic writing test by 80, with the overall percentage of students passing the test reaching 92,7%. As an educative game in this Pandemic Covid-19 period, wordwall can improve students' learning of writing skills at Ps.1 class of LC UIN Malang.